STRATEGI PEMERINTAH DESA DALAM PELAKSANAAN PROGRAM 1.000 TAPAK RUMAH GRATIS DI DESA PALAS KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN TAHUN 2016 - Anton Firdaus; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In February 2016 the Government of Palas Village initiated a program initiative of 1,000 free home footprints that had been agreed with the Village Consultative Board using the funds from the Palas Village Head's donation, the program was given to the poor and unemployed communities, the program of 1,000 free home footprints This is not only for the Palas Village community, but the Palas Village Government also opens opportunities for people from outside the village outside the sub-district. Tread house here is empty land with size 15 m x 20 m = 300 m2 or covering 30 hectares.The purpose of this study is to find out how the strategy of the Palas Village Government in the implementation of the 1.000 second free home footprint program, to find out how the impact of the 1,000 free home footprint program provided by the Palas Village Government for the progress of Desa Palas. In this study, the authors use descriptive research type with qualitative analysis method .. The location of this study was conducted in Palas Village District Pangkalan Kuras Pelalawan District. This research uses the theory of strategy and authority theory. Data collection techniques in this study is by way of interviews and see the documentation to complete the data in this study. Qualitative research method is an option in this study because the author wants mengekplore more in-depth study by looking at the phenomenon and reality that exist in this study.Based on the results of the analysis of this study shows that: the implementation strategy of the program of 1000 free home footprint is done in phases, given the source of funds that only comes from the contribution of the Head of Palas village amounting to approximately Rp.600.000.000, -. Then the building program of 1,000 free home footprint is very good impact on the economic growth of the community of Palas Village and also the progress of Desa Palas.Keywords: Strategy, Village Government